ҚАЗАҚСТАНДАҒЫ ПЛАСТИКАЛЫҚ КАРТОЧКАЛАР НАРЫҒЫНЫҢ ДАМУ ЖАҒДАЙЫ - Макыш, С Б (Journal of Economic Research & Business Administration, 2015)
This article discusses the current state and development of the market of plastic cards in Kazakhstan.